Thrombomodulin activation driven by LXR agonist attenuates renal injury in diabetic nephropathy - Wang, Wei; Wu, Song; Wang, Amanda Y.; Wu, Tao; Luo, Haojun; Zhao, Jia Wei; Chen, Jin; Li, Yi; Ding, Hanlu (Frontiers in Medicine, 2023)
Objective Inflammation and thrombosis are recognized as interrelated biological processes. Both thrombomodulin (TM) and factor XIII-A (FXIII-A) are involved in inflammation and coagulation process. However, their role in the pathogenesis of diabetic nephropathy (DN) remains unclear. In vitro study, the liver X receptor (LXR) agonist T0901317 can up-regulate the expression of TM in glomerular endothelial cells. Now we evaluated the interaction between TM activation and FXIII-A and their effects against renal injury. Methods We first evaluated the serum levels of FXIII-A and TM and the expression of TM, LXR-α and FXIII-A in renal tissues of patients with biopsy-proven DN. We then analyzed the expression of TM, LXR-α and FXIII-A in renal tissues of db/db DN mice after upregulating TM expression via T0901317 or downregulating its expression via transfection of TM shRNA-loaded adenovirus. We also investigated the serum levels of Tumor necrosis factor (TNF)-α, Interleukin (IL)-6, creatinine, and urinary microalbumin level in db/db mice. Results Our study showed that elevations in serum levels of FXIII-A positively correlated to the serum levels of TM and were also associated with end-stage kidney disease in patients with DN. The number of TM+ cells in the renal tissues of patients with DN negatively correlated with the number of FXIII-A+ cells and positively correlated with the number of LXR-α+ cells and estimated glomerular filtration rate (eGFR), whereas the number of FXIII-A+ cells negatively correlated with the eGFR. Conclusion Thrombomodulin activation with T0901317 downregulated FXIII-A expression in the kidney tissue and alleviated renal injury in db/db mice.